PANTOMIM SEBAGAI EKSPRESI DIRI SISWA TUNARUNGU - Nofha - Rina (Widya Komunika, 2019)
The uniqueness of communication ways for the Deaf is different from other people. On communicating they use sign language to bridge communication process. However, not everyone can understand their message so that is difficult to express theirselves. The purpose of this research was to determine the meaning of pantomim by Deaf students and knowing how to self-expressing and meaning by using key informants helped deaf students at SLB Negeri Cicendo Bandung. This research use qualitative method with phenomenological approach. Types of data used are primary data through observation and interview. The results obtained through this research show that the meaning of pantomim by deaf students from five informants are important in his life. Pantomim is entertaining for deaf student, because it is funny and can make them laugh. Pantomim is a hobby that become their favorite thing. So pantomim makes deaf student to be brave, having many friends, and the achievments and make their parents be happy and proud. Through pantomim they can express themselves maximumly with facial expressions, so they can entertain themselves.niqueness of communication ways for the Deaf is different from other people. On communicating they use sign language to bridge communication process. However, not everyone can understand their message so that is difficult to express theirselves. The purpose of this research was to determine the meaning of pantomim by Deaf students and knowing how to self-expressing and meaning by using key informants helped deaf students at SLB Negeri Cicendo Bandung. This research use qualitative method with phenomenological approach. Types of data used are primary data through observation and interview. The results obtained through this research show that the meaning of pantomim by deaf students from five informants are important in his life. Pantomim is entertaining for deaf student, because it is funny and can make them laugh. Pantomim is a hobby that become their favorite thing. So pantomim makes deaf student to be brave, having many friends, and the achievments and make their parents be happy and proud. Through pantomim they can express themselves maximumly with facial expressions, so they can entertain themselves.